1981
DOI: 10.1073/pnas.78.10.6456
|View full text |Cite
|
Sign up to set email alerts
|

Expression of major histocompatibility antigens on pancreatic islet cells.

Abstract: Insulin-dependent diabetes mellitus is often accompanied by manifestations of autoimmunity and is frequently associated with certain HLA haplotypes, predominantly DR3 and DR4. Because the major histocompatibility antigens are important determinants of the immune response in various tissues, we have investigated their expression on the pancreatic islet cells. Human, mouse, or rat islets ofLangerhans, as well as lymphocytes or other differentiated cells, were biosynthetically labeled with radioactive amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The above work suggests that, while pancreatic islets constitutively express low levels of MHC class I (87, 88), the extent of this expression is insufficient for infiltration by CD8+ T cells. Similarly, using a NOD mouse that transgenically expresses the adenovirus E19 protein to inhibit surface MHC class I expression in the β cells, Yamanouchi et al .…”
Section: The Role Of Tissue Conditioningmentioning
confidence: 99%
“…The above work suggests that, while pancreatic islets constitutively express low levels of MHC class I (87, 88), the extent of this expression is insufficient for infiltration by CD8+ T cells. Similarly, using a NOD mouse that transgenically expresses the adenovirus E19 protein to inhibit surface MHC class I expression in the β cells, Yamanouchi et al .…”
Section: The Role Of Tissue Conditioningmentioning
confidence: 99%
“…The possible presence of B cell specific antigens which may be recognized in autoimmune diabetes is currently being studied with xenogenic [12] as well as monoclonal [25] antibodies. Such antibodies have proved useful in the biochemical analysis of transplantation antigens expressed on the B cells [26].…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Although most cells express MHC class I molecules, the expression of class II molecules is restricted to specialized antigen-presenting cells (APC). It has been suggested that the induction of MHC class II on nonlymphoid cells, such as pancreatic beta cells which do not normally express MHC class II molecules [6], could result in the initiation of autoimmunity [7]. Although controversies exist [8±10], it has been reported that islet beta cells from the patients with Type I diabetes mellitus or animals with autoimmune diabetes mellitus express MHC class II antigens [11±13].…”
mentioning
confidence: 99%